2010
DOI: 10.1017/s1049023x00008281
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Maldistribution of Pediatric Medical Resources in Seattle-King County

Abstract: Objective:Seattle-King County (SKC) Washington is at risk for regional disasters, especially earthquakes. Of 1.8 million residents, >400,000 (22%) are children, a proportion similar to that of the population of the State of Washington (24%) and of the United States (24%). The county's large area of 2,134 square miles (5,527 km2) is connected through major transportation routes that cross numerous waterways; sub-county zones may become isolated in the wake of a major earthquake. Therefore, each of SKC's thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A great deal of information about the relationships between the scale of damages in previous disasters and social factors at the community level has already been published [2][3][4][5]. Additionally, hospital surge capacity for critically ill and pediatric patients injured in disasters has been assessed on the basis of geographic information [6][7][8][9]. Several studies have reported associations among predicted casualties in a foreseeable disaster, area characteristics, and hospital surge capacities at the community level in a city [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of information about the relationships between the scale of damages in previous disasters and social factors at the community level has already been published [2][3][4][5]. Additionally, hospital surge capacity for critically ill and pediatric patients injured in disasters has been assessed on the basis of geographic information [6][7][8][9]. Several studies have reported associations among predicted casualties in a foreseeable disaster, area characteristics, and hospital surge capacities at the community level in a city [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…5 , 10 Although dedicated resources for developing triggers for implementing and terminating crisis standards of care are available, the work of developing them is a responsibility of local health-care and government leadership. 11 , 12 Government leadership, in collaboration with health-care experts, is needed to defi ne specifi c criteria for activation of emergency response plans, including when "crisis standards of care" are invoked and when they are terminated, and provide guidance for providers and health-care systems 10 (see "Legal Preparedness" article by Courtney et al 13 in this consensus statement).…”
Section: National Government Support Of Hc/rhas-policymentioning
confidence: 99%
“…All HC/RHAs must be prepared to provide care for large numbers of pediatric patients across their region, and operational plans must account for unique local circumstances ( Fig 4 ). 10 Pediatric consultants should be available to all regional partners by phone or telemedicine for remote consultation. Potential benefi ts of telemedicine communications include improved situational awareness, assistance in field triage, and timely expert consultation.…”
Section: Pediatric Patients and Specialty Populationsmentioning
confidence: 99%